Effects of Neuroendocrine CB1 Activity on Adult Leydig Cells - Cobellis, Gilda; Meccariello, Rosaria; Chianese, Rosanna; Chioccarelli, Teresa; Fasano, Silvia; Pierantoni, Riccardo (Frontiers in Endocrinology, 2016)
Endocannabinoids control male reproduction acting at central and local level via cannabinoid receptors. The cannabinoid receptor CB1 has been characterized in the testis, in somatic and germ cells of mammalian and non-mammalian animal models, and its activity related to Leydig cell differentiation, steroidogenesis, spermiogenesis, sperm quality and maturation. In this short review, we provide a summary of the insights concerning neuroendocrine CB1 activity in male reproduction focusing on adult Leydig cell ontogenesis and steroid biosynthesis.